Localising the Economy as a Resistance Response: A Contribution to the “Resistance Economy” Debate in the Occupied Palestinian Territories - Tariq Dana (17733705) (2020)
Recent years have seen a growing, yet unstructured, debate among Palestinian scholars and activists about the imperative of localising the economic approaches to development. This debate has revolved around the notion of “resistance economy (RE)” that places resistance at the core of the anti-colonial economic consciousness and practice. RE is envisaged as a localised response to the multifaceted crisis—generated by the dynamic interaction among Israel, the Palestinian Authority, and international donors—afflicting the Palestinian political economy. Influenced by the rich legacy of the anti-colonial experience in Palestine, the RE seeks to invigorate organised popular mobilisation and collective struggle against the settler colonial reality. However, the term is still ambiguous and underdeveloped; further, it lacks the theoretical and methodological underpinnings to allow it to be contextualised, strategised, and implemented as part of everyday economic activity. This article seeks to contribute to this debate and foster an understanding that takes into consideration the interrelationship between the economy, politics, and society in a context characterised by the repressive interplay of colonialism and neoliberalism. Finally, the article engages critically with the debate concerning the centrality of agricultural activity to the RE. Other Information Published in: Journal of Peacebuilding & Development License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/1542316620925274